Larvicidal Efficacy of Citrus amblycarpa Peel Extract Against the Larvae of Aedes albopictus - Kasman, Kasman; Ishak, Nuning Irnawulan; Octaviana, Elsi Setiandari Lely; Ridha, Muhammad Rasyid (Diversity: Disease Preventive of Research Integrity, 2022)
Various ways to control dengue vector One of them is by using natural insecticides. The purpose of this study was to test the effectiveness of lime peel powder (Citrus amblycarpa) as an electric mosquito repellent against the death of Aedes albopictus mosquitoes in the field larvae. This study uses a true experimental design conducted at the Tanah Bumbu Health Research and Development Center. The object of this research was lime peel powder (Citrus amblycarpa) which was used as a natural insecticide against the Aedes albopictus mosquito. The larvae used were Aedes aegypti larvae instar III which were hatched at the Research and Development Center of P2B2 Tanah Bumbu and the results of larval collection using ovitrap in the Martapura Health Center Area 1. Susceptibility test for larval mortality and data collection by counting the number of dead Aedes albopictus larvae after being exhibited with skin extract lime for 24 hours at concentrations of 2%, 3%, 4%, and 5%. The LT50 mortality of larvae with lime extract was 2.78 hours (5%), faster than the mortality of larvae in the control group using abate. The results showed the potential of Limau Kuit peel extract as a larvicide in controlling the dengue vector.